OEs vs SIEs: Exploring the cross-cultural adjustment of hotel expatriates in a multicultural society - Halim, Haslina; Abdul Rahman, Nik Adzrieman; Mohamad, Bahtiar (2013)
The study examines the cross-cultural adjustment of organizational and self-initiated expatriates.Specifically, the study aims at identifying whether the two groups of expatriates differ in their adjustment.The focus of the study is on Malaysian hotel expatriates. Since expatriate adjustment is conceptualized as a multifaceted construct encompassing work, general, interaction and overall adjustment, the study also looks at the variations in the patterns of work adjustment, general adjustment, interaction adjustment and the expatriates’ overall adjustment.Two hundred and three expatriates participated in the study, of which, 95 respondents (46.8%) were organizational expatriates (OEs) and 108 (53.2%) were self-initiated expatriates (SIEs).With respect to adjustment, while the data which was drawn from a drop and collect method show some variations in work, general, interaction and overall adjustment, the composite measure of the overall adjustment reveals that, on the whole, respondents are well adjusted to working and living in Malaysia. The results, discussions and limitations of the study are presented in the paper.